Ilmu-Ilmu Ushuluddin UIN Syarif Hidayatullah Jakarta Menatap Masa Depan: Sebuah Pemetaan Keilmuan - Media Zainul Bahri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2018)
This article elucidates the existence of Ushuluddin sciences at UIN Syarif Hidayatullah Jakarta in the past, its developments in form and substance, in appreciating the global developments of Islamic studies, and its connections with the wider academic world. If we look at the development of Ushuluddin’s curriculum, especially since the early 2000s (post-reform era), it appears that the disciplines take part in both national and global trends. However, its academics have not written in international journals indexed by Scopus.I n fact, they are very productive in writing articles in journals at the national level. Presumably, favorable regulations and comprehensive support from the government and universities are not maximized.